Atorvastatin Plus Low-Dose Dexamethasone May Be Effective for Leukemia-Related Chronic Subdural Hematoma but Not for Leukemia Encephalopathy: A Report of Three Cases - Yuan, Jiangyuan; Li, Ying; Liu, Xuanhui; Nie, Meng; Jiang, Weiwei; Fan, Yibing; Xiang, Tangtang; Wang, Hanhua; Quan, Wei; Gao, Chuang; Huang, Jinghao; An, Shuo; et al. (Frontiers in Oncology, 2021)
We are not aware of any reports regarding conservative treatment for leukemia-related chronic subdural hematoma (CSDH). We report our experience with 3 men who were admitted with subdural masses and abnormal leukocyte counts. In two patients, leukemia and CSDH were confirmed on the basis of medical records, mild head trauma, and neuroimaging features. Both patients experienced reduced CSDH and neurological symptoms after receiving atorvastatin (20 mg/day) plus low-dose dexamethasone. However, this combined conservative treatment was ineffective in the third patient, who was diagnosed as having leukemia and showed an increased hematoma volume after two weeks of therapy. Magnetic resonance imaging findings suggested dural metastasis, which prompted a switch from statin-based conservative treatment to chemotherapy. Complete remission of the leukemia and resolution of the subdural mass were observed after chemotherapy, which supported a diagnosis of leukemia encephalopathy. The 5-month follow-ups did not reveal CSDH relapse in all 3 cases. Thus, atorvastatin-based conservative treatment may be effective for leukemia-related CSDH but not for leukemia encephalopathy.